Chemical Stabilisation of Collagen as a Biomimetic - R. Gordon Paul; Allen J. Bailey (The Scientific World Journal)
Collagen is the most abundant protein in animals and because of its high mechanical strength and good resistance to degradation has been utilized in a wide range of products in industry whilst its low antigenicity has resulted in its widespread use in medicine. Collagen products can be purified from fibres, molecules reconstituted as fibres or from specific recombinant polypeptides with preferred properties. A common feature of all these biomaterials is the need for stable chemical cross-linking to control the mechanical properties and the residence time in the body, and to some extent the immunogenicity of the device. This can be achieved by a number of different cross-linking agents that react with specific amino acid residues on the collagen molecule imparting individual biochemical, thermal and mechanical characteristics to the biomaterial. In this review we have summarised the major techniques for testing these characteristics and the mechanisms involved in the variety of cross-linking reactions to achieve particular properties..